Numerical Investigation of the Effect of Geocell-Reinforced Cushion on Load Distribution and Settlement Reduction in Unconnected Piled Raft Foundations - Mojtaba Pourgholamali; Farzin Asgharpour (Firat University Journal of Experimental and Computational Engineering, 2024)
The effect of geocell-reinforced cushion on load distribution and settlement reduction in unconnected piled raft foundations was investigated. Modeling and analysis of various scenarios were carried out using Abaqus software. In this research, a total of nine models, including one connected, three unconnected and unreinforced, and five unconnected and reinforced with geocell, were analyzed. Cushions with thicknesses half of, equal to, and twice that of the foundation were used. The results have shown that optimal outcomes in terms of load distribution efficiency and settlement reduction are achieved when the cushion's stiffness is set at half that of the foundation. The obtained results demonstrate the positive effect of geocell reinforcement in enhancing the performance of unconnected piled raft foundations. The introduction of geocells into the models increases soil stiffness and pile load ratio, consequently enhancing the load-bearing capacity of the piled raft foundation compared to the unreinforced models. The study's findings pave the way for a more effective use of geocells in civil engineering applications, particularly in scenarios demanding high load-bearing capacity and minimal foundation settlement.